Effects and Mechanism of Fe3+ on Flotation Separation of Feldspar and Epidote with Sodium Oleate at Natural pH - Weiwei Zeng; Guofan Zhang; Qing Shi; Leming Ou (Separations, 2022)
The most common beneficiation method for feldspar is flotation with a cationic (amine) collector under acidic conditions. However, there are several disadvantages to this, such as environmental pollution and equipment corrosion. In order to resolve such problems, it is important to study the flotation of feldspar using anionic collectors under natural pH conditions. The purpose of this paper is to study the effects and mechanism of Fe3+ on flotation separation of feldspar and epidote using sodium oleate (NaOL) at a natural pH. Through flotation experiments, adsorption measurements, zeta potential testing, FTIR analysis and X-ray photoelectron spectroscopy (XPS), the mechanism of Fe3+ on the surface of feldspar and epidote is revealed, and the reason behind the difference in flotation of the two minerals is discussed. The flotation test results show that Fe3+ can significantly improve the flotation behavior of minerals when NaOL is used as a collector under natural pH, and the highest recovery rates of feldspar and epidote are 90% and 43%, respectively. Analysis of the solution and adsorption measurement results show that Fe3+ is adsorbed on the minerals′ surface in the form of Fe(OH)3, which promotes the adsorption of NaOL on the minerals’ surface through Fe(OH)3, activating the flotation of feldspar and epidote. The difference in adsorption of Fe3+ between feldspar and epidote is the reason for this difference in flotation behavior. The results of the zeta potentials show that after being treated with Fe3+, the electrostatic adsorption of NaOL displays a significant negative shift on the surface of feldspar, while there is almost no electrostatic adsorption of NaOL on the surface of Fe3+-treated epidote. FTIR analysis confirmed that the difference in the adsorption of Fe3+ and NaOL on the surface of feldspar and epidote is due to the fact that there are more active particles (metal bonds) on the surface of feldspar than on the surface of epidote, and the properties of these metal bonds can be changed by Fe3+, which allows NaOL to be more easily adsorbed on the mineral surface through –COO−. The possible adsorption form is “mineral-Fe3+–COO−“. Compared with the infrared spectrum of epidote, there is a new absorption peak at 1713.68 cm−1, which can be attributed to the C=O characteristic peak of NaOL in the infrared spectrum of Fe3+–NaOL-treated feldspar, which is why the floatability of feldspar is better than epidote. XPS confirmed that the Fe on the surface of feldspar is Fe3+ in the form of Fe(OH)3, while Fe on the surface of epidote is mainly Fe2O3 (Fe–O) contained in mineral crystals. Furthermore, there is less adsorption of Fe3+ on the surface of epidote, and this discrepancy leads to the difference in the adsorption of NaOL on the minerals’ surface, which itself leads to the difference in flotation behavior between feldspar and epidote. These findings indicate that the flotation separation of feldspar and epidote can be achieved using Fe3+ and NaOL under natural pH. This study may provide a reference for the flotation mechanism of feldspar and epidote under natural pH.